2018
DOI: 10.1136/bmjopen-2017-020243
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with 30-day readmission after hospitalisation for community-acquired pneumonia in older patients: a cross-sectional study in seven Spanish regions

Abstract: ObjectiveHospital readmission in patients admitted for community-acquired pneumonia (CAP) is frequent in the elderly and patients with multiple comorbidities, resulting in a clinical and economic burden. The aim of this study was to determine factors associated with 30-day readmission in patients with CAP.DesignA cross-sectional study.SettingThe study was conducted in patients admitted to 20 hospitals in seven Spanish regions during two influenza seasons (2013–2014 and 2014–2015).ParticipantsWe included patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 36 publications
2
65
0
Order By: Relevance
“…In terms of safety and cost, it is important to assess the relationship between initial hospital stay and readmission outcomes [9, 20]. Although the investigation of risk factors is challenging, significant progress has been made on the elderly, that the readmission was found to be largely depends on the comorbidities and factors external to the patient [1, 2, 4, 21]. This has also been observed in children, and one of the identified risk factors is chronic medical conditions such as underlying pulmonary or cardiovascular disease [911].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of safety and cost, it is important to assess the relationship between initial hospital stay and readmission outcomes [9, 20]. Although the investigation of risk factors is challenging, significant progress has been made on the elderly, that the readmission was found to be largely depends on the comorbidities and factors external to the patient [1, 2, 4, 21]. This has also been observed in children, and one of the identified risk factors is chronic medical conditions such as underlying pulmonary or cardiovascular disease [911].…”
Section: Discussionmentioning
confidence: 99%
“…Adult survivors of CAP are at increased risk of death for up to 10 years following recovery, and CAP survivorship is associated with poorer life satisfaction, increased healthcare expenditure, need for domiciliary care, frailty5 and high readmission rates 6. Eleven per cent of older adults are readmitted within 30 days, often for a secondary infection 6. These secondary infections are associated with increased length of stay, mortality and further readmissions 6…”
Section: Introductionmentioning
confidence: 99%
“…Eleven per cent of older adults are readmitted within 30 days, often for a secondary infection 6. These secondary infections are associated with increased length of stay, mortality and further readmissions 6…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts have been put on identification of risk factors for readmission following hospitalization for pneumonia. Comorbidities, socioeconomic status, and so on play a pivotal role in this regard [ 27 , 28 ]; however, to our knowledge, none of the studies identified the association between GI dysfunction during the index hospitalization and risks of readmission. Our finding may not be that unexpected but is pathophysiologically plausible.…”
Section: Discussionmentioning
confidence: 99%